ANALISIS STRATEGI PEMASARAN DENGAN MENGGUNAKAN METODE SWOT DAN QSPM PADA PT. SENTRAL PERKASA JAYA - Wahyudi, Rizky; Purnomo (Journal Knowledge Industrial Engineering (JKIE), 2020)
Sentral Perkasa Jaya is a company that’s move in expedition. The problem faced is the development of technology causing intense business competition, resulting in decreased level of corporate income from year to year. In addition, the strategies used also tend to be monotonous, causing companies to compete with other companies. There are many problem of marketing strategy in the company, it can be an analysis of internal and external factors in the company. Next, internal and external factors will be analyzed again using SWOT matrix and IE matrix. After that Quantitative Strategic Planning Matrix (QSPM) are used to analyze decision making selection about appropriate strategies applied n the company. Based on the calculation of strategies that have been done using two methods, SWOT and IE, then the appropriate alternative strategy for the company is a market penetration strategy and product development strategy. The results of the QSPM method indicate that the best alternative strategy is the product development strategy with a total score of 5.47. This product development strategy is a strategy whereby a company does an existing product repair, or develops a new product to increase sales.